Medicinal plants used against anxiety and hypertension by the indigenous people of Sargodha division and allied areas, Pakistan - Shah, Amin; Rahim, Sarvat; Nosheen, Sahrish; Shahzad, Gulfam (Ethnobotany Research and Applications, 2023)
Background: Anxiety and hypertension are the most severe forms of human psychiatric conditions. Many plants are blessed with medicinal properties to treat anxiety and hypertension, but very little knowledge is available about such plants used by various ethnic communities of Pakistan. This study presents the first report of on plants used to treat anxiety and hypertension among the local communities of Sargodha division and allied areas, using quantitative ethnobotanical indices. Methods: Ethno-medicinal data was collected from aboriginal households who still practice their aboriginal system of medicine. Information of each potential plant and its mode of use to treat anxiety and hypertension were documented using indices frequency citation (FR), preference ranking (PR), percentage of respondents having knowledge (PRK) about the use of species and relative frequency citation (RFC). Results: A total of 57 taxa belonging to 36 families were reported. The highest percentage of life form was herbs (80%). The dominant plant parts were leaves and highest percentage of mode of utilization was paste and decoction. Highest relative frequency citation (RFC) values were Matricaria chamomilla (0.23) while high proportion of respondents (PRK) was reported for Matricaria chamomilla (23.75%). Highest frequency of citation was noted in Matricaria chamomilla (19%). Conclusions: Our study has revealed an intimate relationship between the indigenous flora and livelihood of the people. We hope that information presented in this paper could be used as a baseline data to scientifically verify therapeutic properties and associated bioactive compounds present in the enlisted plants to treat anxiety and hypertension. Keywords: Ethnobotany, medicinal plants, decoction, aboriginal communities